The Eksplorasi Kosmologi Jawa dalam Inovasi Batik Tulis Berbasis Ikonografi Jawa Timur: Kosmolologi Jawa dalam Batik Tulis - Ony Setyawan (Hastagina : Jurnal Kriya Seni, 2026)
This creative work endeavors to present an exploration of Javanese cosmology through the design of hand-drawn batik (batik tulis). Spiritual and ecological values serve as the core elements reflected in the artistic form. The motifs, which mirror Javanese cosmology, are derived from cultural icons found in East Java—a region renowned for its wealth of cultural artifacts, including temples (candi), sacred water springs (petirtaan), and a well-preserved cultural ecology. The creation process follows six systematic stages: reference study, form study, sketching, composition study, production, and dissemination. The interpretation of the work focuses on individual motif elements, color palettes, and structural patterns. The results of the creation and analysis delineate that the Meru, Candi Jawi, and the Tree of Life (Pohon Hayat) serve as the primary motifs representing Javanese cosmological values. These are complemented by supporting motifs such as the lotus flower, the Belahan water spring, and coffee, with connecting motifs appropriated from temple panel ornaments. While these forms have historically existed in traditional batik, this work specifically functions as a medium to sustain a continuous cultural narrative. It offers an interpretation rooted in Javanese philosophy—a depth that is increasingly rare in the batik creations of contemporary artisans.